Psychological, physiological and biochemical markers of the training load and the overtraining effects - Maurício Bara Filho; Renato Miranda; Daniel Schimitz Freitas (Universidade Federal de Santa Catarina, 2009)
Athletic training is a process aimed at breaking the internal balance of the human organism and thus to improve the athlete's performance. However, training stress may result in negative responses such as overtraining syndrome. This maladaptation can be avoided by monitoring the effects of training using psychological, physiological and biochemical variables. No consensus exists regarding the efficiency of some markers, but studies are unanimous that s single marker is unable to monitor and prevent this syndrome. Further studies are necessary to clarify doubts and to broaden the knowledge about this topic, which is of marked interest to researchers involved in high performance sports. Thus, the purpose of this review of the speciali-zed literature was to discuss how psychological, physiological and biochemical markers, such as mood state, overtraining score, resting heart rate variability and creatine kinase, are associated with training load and overtraining.